CURRENT AND POTENTIAL APPLICATIONS OF MODERN TECHNOLOGIES IN MEDICINE AND DENTISTRY AS A CONSEQUENCE OF INDUSTRY 4.0 - Jevtić, Radoje Branislav (HEALTH CARE, 2024)
Industry 4.0, i.e. the fourth industrial revolution, has contributed to enormous progress of knowledge and science in many different areas of life and brought lots of benefits. The aim of this paper is to present the current and potential applications of modern technologies as direct consequence of Industry 4.0 in medicine and dentistry and designing the Medicine 4.0 and Dentistry 4.0 concept. Industry 4.0 has a great influence on every field of modern science, and also on medicine and dentistry. It is obvious that complete healthcare transforms in the totally new, modern and different form - Healthcare 4.0 with a huge benefit from Industry 4.0. This means a better and safer future in the form of optimized medical services and treatment, much bigger percentage of cured patients, virtual medical and dental clinics with telemedicine consultations and lot of other things. Also, industry 4.0 enabled the fast and high-quality production of various types of medical and dental implants, which contributes to a significant reduction in costs. The use of new digital technologies and new concepts enable a completely new approach and better results in medicine and dentistry.
Keywords: Technology, Digitalisation, Industry 4.0, Medicine, Dentistry, Healthcare